Implementations Of Boundary-Domain Integro-Differential Equation For Dirichlet BVP With Variable Coefficient - Nurul Akmal Mohamed; Nur Fadhilah Ibrahim; Mohd Rozni Md Yusof; Nurul Farihan Mohamed; Nurul Huda Mohamed (Penerbit UTM Press, 2024)
Vol. 78 No. 6-5: Sciences and Mathematics Part II